A novel dimorphic pathogen, Emergomyces orientalis (Onygenales), agent of disseminated infection. Issue 5 (27th February 2017) - Wang, Peng; Kenyon, Chris; de Hoog, Sybren; Guo, Lina; Fan, Hongwei; Liu, Hongrui; Li, Zhongwei; Sheng, Ruiyuan; Yang, Ying; Jiang, Yanping; Zhang, Li; Xu, Yingchun
Summary: A novel dimorphic fungus, Emergomyces orientalis sp. nov. a close relative of systemic pathogens in the family Ajellomycetaceae ( Blastomyces, Histoplasma ). The fungus is reported in a 64‐year‐old male from Shanxi, China. The patient developed disseminated skin lesions, productive cough with fever and showed nodular opacities in his left lung on chest radiography. The patient had no identified cause of immunodeficiency apart from type‐2 diabetes mellitus. Clinical, histopathological and mycological characteristics of the agent are given, and its phylogenetic position is determined with multilocus sequence data.